Wynagrodzenia menedżerów a kreacja wartości spółek: Executives remuneration and companies value creation - Mikołajek-Gocejna, Magdalena; Podedworna-Tarnowska, Dorota (Management and Administration Journal, 2021)
Proper design of managers’ remuneration package and information openness in this area have become an increasingly urgent business need, in the time of recent crisis, both in terms of motivating managers to create business value, and rebuilding investors’ trust in companies’ management and the entire financial market. An effective incentive programme, focusing on key success factors for the organization, binds executives’ and shareholders’ objectives, as well as permits to link key people with the company and to attract the best employees in themarket.